Geopolitics and the Governance of International Students: The Evolving Role of Immigration, Refugees and Citizenship Canada (IRCC) in Canadian Policy - Harden-Wolfson, Emma; Zhang, Yvonne (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2026)
This study investigates how Immigration, Refugees and Citizenship Canada (IRCC)’s approach toward international students is evolving in light of shifting geopolitics, using the critically oriented What’s the Problem Represented to Be? approach. Analyzing IRCC announcements from 2022 to 2025 relating to Canada’s global commitments revealed three themes: addressing humanitarian crises, promoting Canadian values, and mobilizing international talent. While IRCC has fulfilled its mandate for immigration, settlement, and meeting Canada’s humanitarian commitments, it has also emerged as a powerful actor in education policy. At the same time, it is actively contributing to foreign policy. However, this is unfolding in ways that are inconsistent and that perpetuate inequalities. This requires equitable and non-oppressive approaches for Canada to enrich higher education and fulfill its global commitments. The study offers insights into the changing nature of Canadian policy making in the mid-2020s, particularly in relation to the new nexus of immigration, education, and foreign policy.